Manière de dire et manière d’exercer la parenté en Kabylie. Pour une approche renouvelée du croisement genre et fait matrimonial - Mohand Anaris (L’Année du Maghreb)
In the anthropology of kinship, the concept of "exchange" is frequently invoked in the analysis of matrimonial practices. Systematized by Claude Lévi-Strauss, this concept was adopted by Pierre Bourdieu to apply to the analysis of his ethnographic data on Kabylie. Due to the scarcity of anthropological studies specifically addressing issues of kinship and matrimonial practices in Kabylie, there has not been a reevaluation of this way of conceptualizing matrimonial practices in the region. This contribution aims to provide a critical examination of the notion of marriage in terms of exchange and the sharing of rights over women.The exercise involves highlighting the limitations of a theory that considers women to only appear in the matrimonial market as objects or symbols whose meaning is constituted outside of them (according to P. Bourdieu) or as the ultimate gift, among those that can be obtained through reciprocal gifts (according to C. Lévi-Strauss). The analysis seeks to elucidate how these propositions primarily concern the way in which male individuals, engage in and perceive matrimonial practices.However, on the other side of the mirror, there are also other logics that do not necessarily pivot around a vision imbued with masculine values. Women also have their way of expressing and practicing kinship. Feminine and masculine logics can then converge, complement, or oppose each other, but, as emphasized by S. Dayan-Herzbrun, it is necessary to distinguish between rituals and codes and the more complex effective practices. It is essential to listen to what those usually categorized as subordinate say and do.The text aims to suggest reflections that integrate the gender dimension, escaping the influence of prevalent logical constructions that sometimes direct the gaze before it has even seen. Drawing on qualitative materials collected during fieldwork conducted between 2009 and 2016 as part of an anthropology thesis, the reflection suggests a more assertive integration of the gender dimension in the interpretation of facts related to kinship.One privileged entry examines the lexical field of "expressing kinship" in Kabylie. The Kabyle’s kinship terminology reveals results that dissociate kinship from a system described as "patrilineal" and "patriarchal". The vocabulary is marked by a matripolarity attested and generalizable to all languages in the Berber area. On another level, the analysis highlights female descriptions of kinship relations. These often demonstrate a reading that almost systematically and intentionally refers to quasi-exclusively female and matrifocal affiliations; the reference ego is often a female individual. Thus, women commonly employ a gynocentric and matrifocal discourse that gives the impression that everything is done by and for women, almost to the exclusion of men.Finally, the study establishes the central and decisive role played by women in matrimonial processes. In conclusion, the elements presented in this article show that matrimonial choices are often oriented based on the interests of groups and/or individuals of both female and male genders involved in each marriage. This reinforces Bourdieu's assertion that the meaning of marriage is read in the strategy that propels it at the moment it is deployed. However, the anthropological interpretation of these strategies can be centered on the worldview of men and their way of seeing and presenting facts in accordance with the code of honor that governs social life. Conversely, when viewed from the perspective of the female ego, the interpretation of kinship relations reveals aspects that dominant classical propositions have long prevented from being seen.